TEACHERS’ ROLE IN 21st CENTURY: TEACHER IS A FACILITATOR, NOT A DICTATOR - Anggraeni, Kartika Ajeng; Yusnita, Rani (LUNAR, 2017)
Teachers’ significant contribution to the success of their students learning leads to some consequences, among those relate to their role and also the teaching–learning process they endorse. Facing the challenges of the 21st century where the teacher is no longer as the sole source of the information for the students impact on the necessity to adjust their role from a ‘dictator’ to a facilitator. This also brings changes to the method on how the teaching–learning process should be conducted. Teacher-centered learning which opened the opportunity for the teacher to act as a ‘dictator’ is no longer appropriate to implement. Rather, teachers should act and position themselves as a facilitator and the appropriate learning method would be student-centered learning. This synergy would enforce the students to be active, critical, independent and creative to face the challenges in their future.